2022
DOI: 10.1007/s10668-022-02347-x
|View full text |Cite
|
Sign up to set email alerts
|

A bibliometric analysis of circular economy in the fields of business and economics: towards more action-oriented research

Abstract: In this paper, we reveal and systemize development trends in the scientific field of the circular economy (CE). Our results imply that academic research on the CE focuses heavily on theoretical conceptualizations and technological solutions. However, these advancements alone are unlikely to help prevent from ecological collapse. With this observation in mind, we explore the potential held by a more relational, action-based approach to support a faster and more efficient transition from the linear economy to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 118 publications
2
16
0
Order By: Relevance
“…The node sizes showed the frequency of the keyword occurrences (Van Nunen et al, 2018 ). A few literature reviews in maritime studies used VOSviewer (e.g., Del Giudice et al, 2021 ; Di Vaio et al, 2022a ), although it was utilized in other research domains as well (Dominko et al, 2022 ).…”
Section: Methods and Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The node sizes showed the frequency of the keyword occurrences (Van Nunen et al, 2018 ). A few literature reviews in maritime studies used VOSviewer (e.g., Del Giudice et al, 2021 ; Di Vaio et al, 2022a ), although it was utilized in other research domains as well (Dominko et al, 2022 ).…”
Section: Methods and Datamentioning
confidence: 99%
“…No study, however, conducted a comprehensive bibliometric investigation to probe into the current status of CE in the literature on sustainability and the maritime industry. Other existing review articles addressed CE in such fields as business and economics (Dominko et al, 2022 ), Industry 4.0 (Okorie et al, 2018 ; Rosa et al, 2020 ), and business models (Centobelli et al, 2020 ; Pieroni et al, 2019 ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…To the best of our knowledge, there are 13 bibliometric analyses published in Environment, Development and Sustainability . These studies are related to sustainability issues in specific industries, such as economics (Dominko et al, 2022 ; Zhao & Zhang, 2022 ; Zárate-Rueda et al, 2021 ), tourism (Diéguez-Castrillón et al, 2022 ), real estate (Lazar & Chithra, 2021 ), agriculture (Dash et al, 2023 ; Mohd Razali et al, 2022 ), and health (Zyoud & Zyoud, 2021 ). While this study considers all sustainability papers published in Environment, Development and Sustainability and it will shed further light on this topic.…”
Section: Introductionmentioning
confidence: 99%
“…Dominko et al systematized the development trends of the scientific field of the circular economy (CE). The authors concluded that academic research on CE is largely focused on theoretical concepts and technological solutions 16 .…”
Section: Introductionmentioning
confidence: 99%